PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muhammad Fajar; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Penelitisn aims to determine the effect of Profitabolitas and Leverage on Stock Price at automotive sub-companies and Components listed on the Indonesia Stock Exchange. Profitability is used as independent variable (X) that is with indicator Return On Asset (ROA), and Leverage with indicator that is Debt to Equity Ratio (DER). While used as the dependent variable (Y) is Price Earning Price Earning Ratio (PER). This research used secondary data that is financial report of Automotive and Components sub sector that listed in Indonesia Stock Exchange (BEI). Sampling was done by sampling the samples used were 12 Automotive and Component sub sector. The technique used is simple linear regression, multiple linear regression, coefficient of determination test, t test, and f test. Data analysis using linear regression analysis with SPSS 21 software. From result of research indicate that variable of Profitability and Leverage partially (t test) does not have an effect on Stock Price in Automotive sub sector and Component company listed in Indonesia Stock Exchange (BEI). The result of simultaneous research (Test f) shows that there is no influence of Profitability and Leverage variable on Stock Price in Automotive and Component sub sector companies listed in Indonesian Stock Exchange.